ANALISIS MAQASID AL-TASARRUFAT AL-MALIYYAH MUHAMMAD AL-TAHIR IBN ASHUR TERHADAP AKAD AL-IJARAH AL-MUNTAHIYAH BI AL-TAMLIK (STUDI PADA PT. BRI SYARIAH KCP PONOROGO) - Mohammad Ridwan (Journal of Islamic Economics (JoIE), 2021)
The writing aims: (1) find an assessment to measure the level of bank compliance with the contract al-Ijarah al-Muntahiya bi al-Tamlik (IMBT) based on maqasid al-tasarrufat al-maliyyah the idea of al-Tahir ibn 'Ashu r, (2) reveals the phenomenon of BRI Syariah KCP Ponorogo compliance with the IMBT contract. The research method used is a qualitative method with a case study type. The type of data in this research is qualitative data on the words and actions of the research subject. Data collection techniques used documentation and unstructured planned interviews. Technique of checking data through credibility test and dependability test. The data analysis technique used Miles and Huberman's analysis with data reduction, data presentation, and conclusion drawing. To make an assessment of the suitability of Islamic banks using the Sekaran method to operationalize maqasid al-tasarrufat al-maliyyah the idea of al-Tahir ibn 'Ashur into dimensions and elements. To develop measurement indicators using the DSN-MUI fatwa. Meanwhile, to obtain a score of compliance with Islamic banks using the balanced scorecard method calculation technique. The findings of this research are BRI Syariah KCP Ponorogo complies with the sharia provisions in the IMBT contract based on maqasid al-tasarrufat al-maliyyah ideas al-Tahir ibn 'Ashur. The level of compliance is 72.5% with the fulfillment of circulation goals of 70%, transparency 68.75%, strength of law 80%, preservation of 75%, and justice 68.75%. This study contributes to a qualitative assessment of sharia compliance based on maqasid al-tasarrufat al-maliyyah ideas al-Tahir ibn 'Ashur as a standard or parameter to assess adherence. Islamic banks in channeling IMBT financing.Penelitian ini bertujuan: (1) menemukan assesmen untuk mengukur tingkat kepatuhan bank terhadap akad al-Ijarah al-Muntahiya bi al-Tamlik (IMBT) berdasarkan maqasid al-tasarrufat al-maliyyah gagasan al-Tahir ibn ‘Ashur, (2) mengungkap fenomena kepatuhan BRI Syariah KCP Ponorogo terhadap akad IMBT. Metode penelitian yang digunakan adalah metode kualitatif dengan tipe studi kasus. Jenis data penelitian ini adalah data kualitatif kata-kata dan tindakan subjek penelitian. Teknik pengumpulan data menggunakan dokumentasi dan wawancara terencana tidak terstruktur. Teknik pemeriksaan data melalui uji kredibilitas dan uji dependibilitas. Teknik analisis data menggunakan analisis Miles dan Huberman dengan reduksi data, penyajian data, dan pengambilan kesimpulan. Untuk membuat assesmen kesesuaian bank syariah menggunakan metode Sekaran untuk mengoperasionalisasi maqasid al-tasarrufat al-maliyyah gagasan al-Tahir ibn ‘Ashur menjadi dimensi dan elemen. Untuk mengembangkan indikator pengukuran menggunakan fatwa DSN-MUI. Sedangkan untuk memperoleh skor kepatuhan bank syariah menggunakan Teknik perhitungan metode balanced scorecard. Temuan penelitian ini adalah BRI Syariah KCP Ponorogo patuh terhadap ketentuan syariah dalam akad IMBT berdasarkan maqasid al-tasarrufat al-maliyyah gagasan al-Tahir ibn ‘Ashur. Tingkat kepatuhannya sebesar 72.5% dengan pemenuhan tujuan sirkulasi 70%, transparansi 68.75%, kekuatan hukum 80%, preservasi 75%, dan keadilan 68.75%. Penelitian ini berkontribusi pada assesmen kepatuhan syariah secara kualitatif berdasarkan maqasid al-tasarrufat al-maliyyah gagasan al-Tahir ibn ‘Ashur sebagai standar atau parameter untuk menilai kepatuhan Bank syariah dalam menyalurkan pembiayaan IMBT.